Efekty rządowego programu "Rodzina 500 plus" dla rodzin i aktywności zawodowej kobiet = Effects of the "Family 500+" government programme for families and for the professional activity of women - Turkowska-Kucharska, Wioleta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
It has been a year since the government launched the "Family 500+" ("?Rodzina 500+") programme. Already at the stage of the debate, the idea evoke extreme emotions: from very positive to extremely negative ones, among both politicians and public opinion. Today, from the perspective of time and observation of the programme functioning, its first effects are noticeable. The author of this article uses the project method. The article discusses the influence of the 500+ benefits on the life of Polish families and of the youth at the early-adulthood age, as well as how the programme determines women`s professional activity, and thereby the labour market.
Keywords: program 500 plus; rodzina; młodzież; kobieta; aktywność zawodowa; 500+ programme; family; youth; woman; professional activity